Role-Playing Method for Students' Interpersonal Communication Improvement - Risqi Ekanti Ayuningtyas Palupi; Budi Purwanto; Tri Wuryanto (Pusat Riset dan Inovasi Nasional, 2023)
Interpersonal communication involves interaction between two or more people, usually with a direct connection and with some sort of relationship being assumed. Interpersonal communication is often distinguished from group communication, organizational communication especially in corporate or business settings, public communication, or mass communication. The lack of students’ communication activities signed by the students’ commonly shy to speak up or delivering their idea. Most of them have a high anxiety in speaking. It also supports with there are no activities outside classroom in enhancing their capacity in speaking. The important thing to remember is that interpersonal communication is not part of an innate personality trait, but is a skill that can be learned and trained. This research aims to improve the ability of interpersonal communication by role playing method for second year students of Digital Business and Disaster Management Program of Akbara Polytechnic. This research is a Classroom Action Research. Subject of this research is 20 students. The data collection methods are test and observation. The first cycle of role-playing action is based on the drama script. The first and the second cycle focused on the aspect of speaking ability especially for grammar, diction/vocabulary, pronunciation, fluency, and comprehension. The second cycle of role-playing action is based on the drama script but the students’ roles are changed. The second cycle is focused on the aspect of equality which is still lack of it. The improvement of the teaching learning process can be shown by the result of students’ speaking observation such as the students being active to deliver their character, use the correct grammar, delivering the message of the character fluency and comprehension, minimum the hesitation, and use various vocabularies. Moreover, the improvement also can be seen form the students’ average test score of speaking, they are: (1) the students’ average pre-test score is 60,4; (2) the students’ average post-test score on the first cycle is 73,8; (3) the students’ average post-test score on the second cycle is 89,5. It can be concluded that role-playing method can enhance the students’ ability of interpersonal communication for student of second grade students of Digital Business and Disaster Management Program of Akbara Polytechnic.